PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KEAKTIFAN MATEMATIS MATERI LINGKARAN PADA SISWA SMP - Novitasari, Julia; Pujiastuti, Heni (PATTIMURA UNIVERSITY, 2020)
Student activeness in the class student of VIII H SMPN 1 Ciruas second term 2019/2020 year on mathematics subjects on circle material still in percentage 59,64% of the total 33 students, so that result less than expected value by researcher which is 65%. Based on these problems, it is necessary to make improvements to the learning model. For that researchers conduct research with the purpose to increase student activity in mathematics. Method of research is classroom action research. The object of the research is the application of the snowball throwing model. This research was conducted in two cycles, cycle I consists of one meeting and cycle II consists of two meetings. Stages in this cycle is (1)Planning, (2)Action, (3)Observer, (4)Reflection. The data collection method used were observation, questionnaires and documentation. Based on the results of data analysis by descriptive quantitative obtained, that an increase in student activity with a percentage of activity in cycle I to cycle II. Cycle I from the observations of researchers, it was found that the results of student activeness were equal to 45,88% and from the questionnaire is 59,64%. Then on cycle II reaches a value of 67,09% from the activeness standard set by the researcher which is 65%. So that the percentage in crease can be obtained from the cycle I to cycle II. The conclusion is that by applying the snowball throwing learning model on learning mathematics circle material in class student VIII H SMPN 1 Ciruas an increase in student activity.